Meningkatkan pemahaman mahasiswa terhadap manajemen pemasaran melalui metode pembelajaran peta konsep (mind mapping) - Azhari, Devi Syukri (Jurnal Kajian Manajemen Bisnis, 2020)
This research aims to improve the quality of Marketing Management learning, to enhance student enthusiasm for learning, to improve lecturers' skills in developing learning models and media, and to improve student learning achievement. The results showed that students' learning achievements experienced an increase in each cycle. Mastery of student learning before applying the concept map method 0%, after applying the concept map method, mastery learning from students after the final test is 9 4%. Interest, activeness, and collaboration of students in the learning process with a range of 1-4 results are good (3.44). The results of observations on the skills of lecturers in the management of learning using the concept map method with a range of 1-4 show good results with the mean of cycle 1, cycle 2, and cycle 3, 38. The score is the average of all aspects observed in three cycles.Keywords:Marketing management; mind mapping learning method.